Monarch butterflies use an environmentally sensitive, internal timer to control overwintering dynamics - Green, Delbert A. (Mol Ecol, 2019)
The monarch butterfly (Danaus plexippus) complements its iconic migration with diapause, a hormonally controlled developmental program that contributes to winter survival at overwintering sites. Although timing is a critical adaptive feature of diapause, how environmental cues are integrated with genetically-determined physiological mechanisms to time diapause development, particularly termination, is not well understood. In a design that subjected western North American monarchs to different environmental chamber conditions over time, we modularized constituent components of an environmentally-controlled, internal diapause termination timer. Using comparative transcriptomics, we identified molecular controllers of these specific diapause termination components. Calcium signaling mediated environmental sensitivity of the diapause timer, and we speculate that it is a key integrator of environmental condition (cold temperature) with downstream hormonal control of diapause. Juvenile hormone (JH) signaling changed spontaneously in diapause-inducing conditions, capacitating response to future environmental condition. Although JH is a major target of the internal timer, it is not itself the timer. Epigenetic mechanisms are implicated to be the proximate timing mechanism. Ecdysteroid, JH, and insulin/insulin-like peptide (IIS) signaling are major targets of the diapause program used to control response to permissive environmental conditions. Understanding the environmental and physiological mechanisms of diapause termination sheds light on fundamental properties of biological timing, and also helps inform expectations for how monarch populations may respond to future climate change.